The readiness among the polytechnic engineering and non-engineering lecturers towards implementation of 4C in teaching - Awang, Noor Hidayah; Ming, Foong Lee (2020)
The paper discusses the readiness level of the 4C polytechnics lecturer (creative, critical, communication & collaboration) from the cognitive, psychomotor and affective domains. By using questionnaires as an instrument, this research employed the survey as research design. A total of 332 lecturers in polytechnics were randomly selected randomly as respondents. The results show that polytechnic lecturers tend to have a high level of readiness for 4C for all three domains. Findings also show that, except for the psychomotor and affective domain, there is no substantial difference in cognitive domain for 4C between engineering and non-engineering lecturers. In short, the preparation of 4C skills among the polytechnic lecturers is necessary to ensure that graduates are successful in today's workplace.